Aceh Conflict Resolution, Actions of Non-GAM Acehnese in Peace in Veranda of Mecca Post-MoU. Helsinki - Rukaya Rukaya; Alexius Aan; Sherley Chintya; Nina Ayuni; Okta Putri; Heni Kuswati; Nur Sutari; Hesky Septiawan; Ariya Winandar; Dede Yas Putra; Jagad Aditya Dewantara (CV. Rayyan Dwi Bharata, 2023)
Following several years of world political leadership beset by clashes between nations, the trend lately is to spread invisible turmoil within a nation, such as between ethnic struggles and withdrawal or rebellion. New issues in the globalization cycle are related to issues of basic freedoms, political, monetary and social changes, followed by the development of different struggles. According to social researcher Hugh Miall,